2017
DOI: 10.1016/j.celrep.2017.10.095
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Translational Remodeling during Human Neuronal Differentiation

Abstract: Summary Faithful cellular differentiation requires temporally precise activation of gene expression programs, which are coordinated at the transcriptional and translational levels. Neurons express the most complex set of mRNAs of any human tissue, but translational changes during neuronal differentiation remain incompletely understood. Here, we induced forebrain neuronal differentiation of human embryonic stem cells (hESCs) and measured genome-wide RNA and translation levels with transcript-isoform resolution.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 78 publications
(114 reference statements)
18
105
0
Order By: Relevance
“…Alternatively, intronic sequences could act to recruit factors to inhibit translation, activate degradation during translation, or both. Analysis of the translation of splice variants with ribosome profiling found that intron retention events within the coding regions of transcripts were poorly translated (Weatheritt et al, 2016), consistent with our findings that transcripts with retained introns are often only bound by a single ribosome (Fig 6A) and other polysome fractionation studies (Floor & Doudna, 2016; Blair et al, 2017). Further study of the fate of transcript with retained introns will lead to a better understand of the true diversity of roles intron retention plays in gene expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Alternatively, intronic sequences could act to recruit factors to inhibit translation, activate degradation during translation, or both. Analysis of the translation of splice variants with ribosome profiling found that intron retention events within the coding regions of transcripts were poorly translated (Weatheritt et al, 2016), consistent with our findings that transcripts with retained introns are often only bound by a single ribosome (Fig 6A) and other polysome fractionation studies (Floor & Doudna, 2016; Blair et al, 2017). Further study of the fate of transcript with retained introns will lead to a better understand of the true diversity of roles intron retention plays in gene expression.…”
Section: Discussionsupporting
confidence: 90%
“…Several models have been proposed to explain what marks a stop codon as authentic, where termination of translation occurs normally, versus a premature termination codon (PTC), which leads to NMD in animals, yeast and plants (Nagy & Maquat, 1998; Amrani et al, 2004; Bühler et al, 2006; Behm-Ansmant et al, 2007; Kérenyi et al, 2008; Singh et al, 2008; Hogg & Goff, 2010; Drechsel et al, 2013; Lloyd et al, 2018). Alternative splicing has a well known role in altering the coding potential of transcripts, but can also alter the translation efficiency of the transcript (Floor & Doudna, 2016; Weatheritt et al, 2016; Blair et al, 2017; Fagg et al, 2017; Reixachs-Sole et al, 2019) or change the stability of transcripts by targeting them to NMD (Jumaa & Nielsen, 1997; Hilleren & Parker, 1999; Lejeune et al, 2001; Lewis et al, 2003; Lareau et al, 2007; Ni et al, 2007; Floor & Doudna, 2016; Reixachs-Sole et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Using branched FISH, high-resolution confocal microscopy, and volumetric quantification of mRNA foci, we show that wild-type Htt mRNAs (with a normal number of CAG repeats) accumulate in the nucleus of neuronal cells, but not in non-neuronal cells. A similar Htt distribution pattern was demonstrated by the analysis of RNA sequencing (RNA-seq) datasets from human embryonic stem cell (HESC)-derived neurons (Blair et al, 2017; Figure S3E). The results showed that, relative to the total number of reads in each sample, Htt transcript is detected more often in the nuclear fraction than in the cytoplasmic fraction.…”
Section: Discussionsupporting
confidence: 72%
“…Processed nuclear and cytoplasmic RNA-seq datasets across neuronal differentiation from (Blair et al, 2017) were downloaded from the Gene Expression Omnibus (GSE100007) and TPM values for Htt mRNA (ENSG0000197386) were extracted for plotting.…”
Section: Quantification and Statistical Analysismentioning
confidence: 99%
“…Binding sites (and their relative strengths) identified by these methods represent numerical averages over numerous mRNA isoforms, some of which might not even contain the actual binding sites. Isoform-specific association data are important because differential mRNP binding is thought to underpin many of the functional differences observed in same-gene isoforms, including variable translational efficiency, cellular localization, and stability (Blair, Hockemeyer, Doudna, Bateup, & Floor, 2017;Geisberg, Moqtaderi, Fan, Ozsolak, & Struhl, 2014). Alterations in distributions of isoforms whose sequences differ upstream of cleavage/polyadenylation sites (mRNA 3 isoforms) can contribute to misregulation of cell growth and differentiation and to increased oncogenic potential (Mayr, 2017).…”
Section: Introductionmentioning
confidence: 99%